An investigation of intrinsic and extrinsic motivation towards the level of employees' job satisfaction at Majlis Perbandaran Bentong (MPB), Bentong Pahang Darul Makmur / Ezureen Faziatul Ashikin Abd Razak - Abd Razak, Ezureen Faziatul Ashikin (Faculty Of Business Management, 2016)
The study was conducted in order to identify the relationship between employee motivation and job satisfaction. There are two types of motivation which are extrinsic motivation and intrinsic motivation. According to the previous researchers, motivations depend on the employees' job satisfactions. If employees do not feel motivated, they will not feel fully satisfied with their jobs. The instrument used to conduct this survey was by distributing the questionnaires. The questionnaires were distributed to ninety-five (95) respondents in MajIis Perbandaran Bentong (MPB) by using the simple random sampling technique. The findings of the data are clearly shows that the mean of the employees at MajIis Perbandaran Bentong (MPB) is moderately high and there is significant relationships between motivational factors and employee's job satisfaction. Therefore the alternate hypothesis is accepted. It can be concluded that the majority of the respondents in MajIis Perbandaran Bentong was female and most of them were married. Most of the respondents were SPM holders and age between 36 years old to 44 years old with 1 to 5 years of working experience. The findings show that social relationship is the most significant among all those four motivation. Social relationship can be refer as the interpersonal relationship with the society which an individual will have more interaction with his or her job to develop more creative ideas in the organization. To conclude, social relationship among employees in MajIis Perbandaran Bentong (MPB) was high. After the data were collected and analyzed, the purpose of recommendation for the organization is to increase the monetary rewards in order to motivate the employees to perform the work efficiently.